Interplay Between Gluten, HLA, Innate and Adaptive Immunity Orchestrates the Development of Coeliac Disease - Voisine, Jordan; Abadie, Valérie (Frontiers in Immunology, 2021)
Several environmental, genetic, and immune factors create a “perfect storm” for the development of coeliac disease: the antigen gluten, the strong association of celiac disease with HLA, the deamidation of gluten peptides by the enzyme transglutaminase 2 (TG2) generating peptides that bind strongly to the predisposing HLA-DQ2 or HLA-DQ8 molecules, and the ensuing unrestrained T cell response. T cell immunity is at the center of the disease contributing to the inflammatory process through the loss of tolerance to gluten and the differentiation of HLA-DQ2 or HLA-DQ8-restricted anti-gluten inflammatory CD4+ T cells secreting pro-inflammatory cytokines and to the killing of intestinal epithelial cells by cytotoxic intraepithelial CD8+ lymphocytes. However, recent studies emphasize that the individual contribution of each of these cell subsets is not sufficient and that interactions between these different populations of T cells and the simultaneous activation of innate and adaptive immune pathways in distinct gut compartments are required to promote disease immunopathology. In this review, we will discuss how tissue destruction in the context of coeliac disease results from the complex interactions between gluten, HLA molecules, TG2, and multiple innate and adaptive immune components.